Political and Anti-political War Films. A comparative analysis of Apocalypse Now and The Battle of Algiers - Iglesias Turrión, Pablo (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This article is a comparative analysis of the “colonized Other”, what is represented in two films; Coppola´s “Apocalypse Now” and Pontecorvo´s “The battle of Algiers”. Using some concepts of Fanon classical study about Colonialism “The Wretched of the earth” (Les Damnés de la Terre), I doubt whether the aesthetics of violence in Coppola´s film represents the “Other” as a subaltern character. In “Apocalypse Now” the power of enunciation is on the side of the colonial narrator. On the other hand, in Gillo Pontecorvo’s film, with documentary aesthetics, the Algerian National Liberation War represents the “colonized Other” as a powerful political subject. The article explores the importance of films as generator of political imaginaries of Colonialism and the national liberation processes. In the present context with military interventions in Iraq or Afghanistan and new films about those, again the problem of how the Other should be represented is emerging.